Autoevaluación del Sistema de Control Interno (2019)
Control Self-Assessment is an element of the Internal Control System which allows the organizational diagnose and strengthening. It is run throughout the entity and supposes the support from the high managerial circle. This support is in the form of physical resources and the orientation offered throughout its execution. Self-assessment generates enhanced staff responsibility as it involves them in the analysis of the strengths and weaknesses of the system, in the collection of the data supporting the description of the state of the system and as it allows them to propose improvement plans that contribute in the achievement of the Control System goal and thence the organization’s goal. Difficulties in its application may stem from aspects related to the organizational culture: if the staff is not willing to collaborate with the supporting groups in furnishing the information, if there is apathy to the process, and if there are not the skilled people to carry out the process. The process is carried out in three stages: the first one is the planning, in which the Self-Assessment Committee involves the management and assigns activities and responsibilities; it also defines the work time table, the necessary resources and trains the supporting groups. The second stage refers to the execution, which consists in getting the information that supports the analysis of every element of the Control System and allows the expression of objective statements about their performance. Finally, the third stage is the production of a report, which accounts for the results of the Control System Self-Assessment, its development and difficulties, and status improvement proposals.